Impact of obesity on functional and oncological outcomes in radical perineal prostatectomy - Altay, Bülent; Erkurt, Bülent; Güzelburç, Vahit; Kiremit, Murat Can; Boz, Mustafa Yücel; Albayrak, Selami (Canadian Urological Association, 2015)
Introduction: We evaluated the impact of obesity on perioperative morbidity, functional, and oncological outcomes after radical perineal prostatectomy (RPP). Methods: A total of 298 consecutive patients underwent RPP at our institution. Patients were categorized into 3 groups based on their body mass index (BMI): Normal weight < 25 kg/m(2) (Group 1), overweight 25 to < 30 kg/m(2) (Group 2), and obese >= 30 kg/m(2) (Group 3). We compared the groups with respect to perioperative data, postoperative oncologic, and functional outcomes. Evaluation of urinary continence and erectile function was performed using a patient-reported questionnaire and the International Index of Erectile Function-5 questionnaire, respectively, administered pre-operatively and at 3, 6, and 12 months. Limitations included short follow-up time, retrospective design and lack of a morbidly obese group. Results: No significant differences were found among the 3 groups with regard to operative time, estimated blood loss, length of hospital stay, catheter removal time, positive surgical margin, and complication rates. At 12 months, 94.7%, 95% and 95% of normal, overweight and obese patients, respectively, were continent (free of pad use) (p = 0.81). At 12 months, 30.6%, 29.8% and 30.4% of patients had spontaneous erections and were able to penetrate and complete intercourse in Group 1, Group 2, and Group 3, respectively (p = 0.63). Conclusions: In this cohort of patients, no clinically relevant risks were associated with increasing BMI.
WOS: 000373177500002
PubMed ID: 26600881
Keywords: Impact of Obesity; Radical Perineal Prostatectomy